RATIONAL THERAPY OF CHILDREN'S CROUP - M.D. Bakradze; A.S. Darmanyan; V.K. Tatochenko (Вопросы современной педиатрии)
Basing upon proprietary research including data on 130 patients with acute steno sing laryngotracheobronchitis, the authors conclude that the usage of systematic and topical glucocorticosteroids promotes reduction of upper air passages obstruction within 24chour period among 83% of patients. Inhalation with moistened air is inefficient and cannot be considered as an independent method for croup therapy. In this research, 14% of patients took antibiotics: in most cases with evident or probable bacterial infection; with no evident signs — just about 3% of patients took the medication. For children with bacterial infections accompanying croup, the introduction of antibiotics had no effect on the croup symptoms dynamics.Key words: acute stenosing laryngotracheobronchitis, children, curing, glucocorticosteroids, antibiotics.